Świadomość i przekonania ojców na temat współczesnych zagrożeń i bezpieczeństwa dzieci = The awareness and conviction of the fathers on contemporary risks and safety of children - Urmański, Jan; Wac, Katarzyna (Journal of Education, Health and Sport, 2017)
Urmański Jan, Wac Katarzyna. Świadomość i przekonania ojców na temat współczesnych zagrożeń i bezpieczeństwa dzieci = The awareness and conviction of the fathers on contemporary risks and safety of children. Journal of Education, Health and Sport. 2016;6(11):412-429. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.169555 http://ojs.ukw.edu.pl/index.php/johs/article/view/4017 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 26.11.2016. Świadomość i przekonania ojców na temat współczesnych zagrożeń i bezpieczeństwa dzieci The awareness and conviction of the fathers on contemporary risks and safety of children Jan Urmański, Katarzyna Wac1 1Katedra Psychologii Emocji i Motywacji, Katolicki Uniwersytet Lubelski Jana Pawła II 1Department of Emotion and Motivation Psychology, The John Paul II Catholic University of Lublin STRESZCZENIE Wprowadzenie: Współcześnie obserwuje się coraz bardziej zróżnicowane niebezpieczeństwa i zagrożenia, na które narażone są dzieci. Troska ze strony rodziców jest kluczowym czynnikiem chroniącym bezpieczeństwo dzieci. Szczególne znaczenie w wychowaniu i ochronie dzieci ma aktywna postawa ojców. Cel pracy: Zbadać świadomość oraz przekonania ojców na temat współczesnych zagrożeń i bezpieczeństwa dzieci i młodzieży. Zanalizować stan wiedzy ojców co do potencjalnych zagrożeń oraz stopień ich zaangażowania w wychowywanie dzieci. Materiał i metoda: Przeprowadzone zostało badanie ankietowe na grupie 439 ojców posiadających co najmniej jedno dziecko poniżej 18 roku życia. Została opracowana specjalna ankieta badawcza składającą się z 11 pytań, w tym trzech otwartych, oraz metryczki stanowiącej opis podstawowych cech społeczno-demograficznych respondenta. Wyniki: Wyniki badań wskazały na istotne różnice pomiędzy grupą ojców reprezentujących próbę ogólnopolską a tzw. aktywnymi, wyróżniającymi się większym zaangażowaniem w wychowywanie dzieci. Wnioski: Do kluczowych wniosków należy przede wszystkim wskazanie przez 94% ojców aktywnych przekonania co do wpływu na bezpieczeństwo dzieci. O 33% mniej ojców z grupy ogólnopolskiej zadeklarowało takie przekonanie. Można wnioskować, że aktywna postawa względem bycia ojcem silnie koreluje z poczuciem sprawczości. Ponadto ojcowie reprezentujący próbę ogólnopolską wskazują na inne źródła niebezpieczeństw niż ojcowie tzw. aktywni, w których ocenie pierwotnym źródłem niebezpieczeństwa dla młodego pokolenia jest brak silnej relacji rodzic – dziecko. Słowa kluczowe: współczesne zagrożenia, bezpieczeństwo dzieci, zaangażowane ojcostwo ABSTRACT Introduction: Today observed increasingly diverse dangers and threats to which children are exposed. The concern of parents is a key factor in protecting the safety of children. Of particular importance in the education and protection of children are proactive fathers. Objective: Examine the awareness and conviction of the fathers on the current risks and safety of children and youth. Analyze the state of the fathers of the potential threat and the degree of their involvement in raising children. Material and methods: survey has been conducted on a group of 439 fathers with at least one child under 18 years of age. It was developed a special research survey consisting of 11 questions, including three open, and the specifications which is the description of basic socio-demographic characteristics of the respondent. Results: The results showed significant differences between the group of fathers in the representative sample and the so-called active fathers, distinctive greater involvement in bringing up children. Conclusions: The key conclusion is that 94% of active fathers beliefs about the impact on the safety of children. About 33% less of representative fathers declared such a belief. It can be concluded that the active attitude toward being a father strongly correlates with a sense of effectiveness. In addition, fathers representing a representative sample attempt to suggest other sources of danger than involved fathers, in which the assessment of the primary source of danger for the young generation is the lack of a strong parent - child relationship. Keywords: contemporary risks, child safety, involved fatherhood